1989
DOI: 10.1007/bf02556062
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of genes in chick growth cartilage detected byin situ hybridization

Abstract: We have used in situ hybridization to examine expression of collagen type I, II, and X mRNA and osteonectin mRNA in the chick epiphysis. Tissue samples from the proximal tibial growth cartilage were fixed in modified Carnoy's solution, dehydrated in ethanol, and embedded in paraffin. Longitudinal and transverse sections were demineralized with HCl and digested with hyaluronidase and proteinase K. In situ hybridization was carried out using biotinylated cDNA probes; the hybridized probe was detected using a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…After 30 days, both types I and X collagen were present in the cell layer, whereas the rate of synthesis of type II collagen and the alkaline phosphatase activity were very low. The presence of type X collagen was not associated with cell hypertrophy, in accordance with results obtained in vivo in the chick growth plate [Oshima et al, 1989] and in vitro with immature sternal chondrocytes [Pacifici et al, 1991a,b] or with cells isolated from the mandibular ectomesenchyme [Ekayanake and Hall, 1994]. Similar data on proliferation, the expression of types I and II collagen genes and the synthesis of these types were observed [Daniel et al, 1984;Hering et al, 1994] with adolescent bovine articular chondrocytes plated at high density and grown in the presence of ascorbic acid.…”
Section: Discussionsupporting
confidence: 91%
“…After 30 days, both types I and X collagen were present in the cell layer, whereas the rate of synthesis of type II collagen and the alkaline phosphatase activity were very low. The presence of type X collagen was not associated with cell hypertrophy, in accordance with results obtained in vivo in the chick growth plate [Oshima et al, 1989] and in vitro with immature sternal chondrocytes [Pacifici et al, 1991a,b] or with cells isolated from the mandibular ectomesenchyme [Ekayanake and Hall, 1994]. Similar data on proliferation, the expression of types I and II collagen genes and the synthesis of these types were observed [Daniel et al, 1984;Hering et al, 1994] with adolescent bovine articular chondrocytes plated at high density and grown in the presence of ascorbic acid.…”
Section: Discussionsupporting
confidence: 91%
“…Over a 5-day period, there was little change in activity. In previous studies, we had assessed type II and X collagen expression by these cells and found that both transcripts were abundantly expressed by the hypertrophic cells (Oshima et al, 1989). Type II collagen was expressed early, while type X was expressed strongly toward the end of the culture period.…”
Section: Phenotypic Characteristics Of Embryonic Chondrocytesmentioning
confidence: 94%
“…These include 1) the acquisition of synthesis of collagen type X (Schmid and Conrad, 1982a;Schmid and Linsenmayer, 1983;Capasso et al, 1984;Gibson et al, 1984); 2) the loss of synthetic capacity for collagen types I1 and IX (Oshima et al, 1989;Linsenmayer et al, 1991) with concomitant covalent crosslinking of type I1 ; 3) a decrease in proteoglycan synthesis with the complete loss of a small proteoglycan, PG-Lb (Shinomura et al, 1984;Shinomura and Kimata, 1992); and 4) an increase in activity of metalloproteinases (Sakiyama et al, 1994) and alkaline phosphatase and calcification of cartilage Stein et al, 1990;Wuthier and Register, 1995). Other up-regulated proteins identified largely by biochemical and immunological methods include the C-raf protooncogene (Kaneko et al, 19941, the first component of complement CIS (Sakiyama et al, 1994), and members of the TGF-p (Loveridge et al, 1993;Dodds et al, 1994) and transglutaminase families (Aeschlimann et al, 1993).…”
Section: Introductionmentioning
confidence: 98%